Recognition and Analysis of the Effective Social Dimensions on the Tendency of Rural Youths to Addiction in Rural Areas of Isfahan City - Ahmad Hajarian; Yosef Qanbari (Drug Control Headquarters, Research and Education Office, 2013)
Objective: The object of this study was the identification of effective factors and the prevalence of drug use among rural youths. Method: The study was a scientific-comparative research. The sample was 450 rural youths from the city of Isfahan. The related questionnaires were collected in 15 villages of Isfahan city. Findings: Results showed that between family factors and consumption rate, family rift and family dependency and father's occupational status were effective ones. Also, among the social and emotional factors anomaly, tendency to religious issues and friendship with those addicted to drugs have been effective in getting addiated of rural youths. Among personal factors, the increase of education level can act as an effective factor. Conclusion: the results showed that between tnndency to religious factors and consumption rate there is a negative meaning. Similarly, there is a positive meaning among unemployment, stablishing friendship with addicted, being close to urban places and addiction to drugs.